Pengaruh Brand Image, Product Involvement, dan Brand Engagement Terhadap Purchase Intention Teh Pucuk di Kota Jakarta - Annisa Intan Ramadhan dan Chairy (Jurnal Manajemen Bisnis dan Kewirausahaan, 2020)
This research aims to find out influence of Brand Image, Product Involvement, and Brand Engagement to Teh Pucuk’s Purchase Intention in Jakarta. Research conducted by distributing questionnaires to 272 respondents randomly. Analysis technique used is technique of quantitative analysis. Data of this research was taken from August until Dec 2018. The research data was analyzed by SmartPLS application. The results showed that Brand Image, Product Involvement, and Brand Engagement had significantly influence on Teh Pucuk’s Purchase Intention. The population in this study were people living in Jakarta, researchers took samples of 272 respondents using the questionnaire method. The sampling technique used is simple random sampling, where each element of the population has the same opportunity to be selected as a sample. Brand Engagement had influence Purchase Intention; Brand Image had influence Brand Engagement; Brand Image had influence Purchase Intention; Product Involvement had influence Brand Engagement; and Product Involvement had influence Purchase Intention. Also this research had indirect effect, that Brand Engagement had influence as mediator between Brand Image and Purchase Intention and Product Involvement and Purchase Intention.